2004
DOI: 10.1097/01.blo.0000144971.12731.a2
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Osteoarthritis

Abstract: Joint damage occurs when structures protecting the joint fail. Because osteoarthritis consists of end-stage joint damage, I propose that risk factors for disease can be best understood as either impairments of joint protectors, increasing joint vulnerability, or as factors that excessively load the joint, leading to injury. I review current knowledge using this paradigm, separating factors into those increasing joint vulnerability (malalignment, muscle weakness, genetic and ethnic predispositions, aging) and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
1
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(43 citation statements)
references
References 25 publications
1
39
1
2
Order By: Relevance
“…While the exact etiology of OA is unknown, it has been associated with non-bilateral recurring motion injuries on joint surfaces (Bridges, 1992;Bridges, 1995;Cope et al, 2005;Felson, 2004;Felson et al, 1991;Felson and Zhang, 1998;Gramstad and Galatz, 2006;Huiskes, 1982;Jurmain, 1999;Larsen, 2000;Schrader, 2012;Weiss and Jurmain, 2007). OA has been used in prior bioarchaeological research to discuss task-based repetitive motion injuries within joints, estimating motions used over and over again, such as grinding grain or weaving textiles (Bridges, 1989;Bridges, 1991a;Bridges, 1992;Cope et al, 2005;Jurmain, 1999;Kennedy, 1989;Klaus et al, 2009;Larsen, 2000: 107, Pearson andRoberts and Manchester, 1995: 150 and others).…”
Section: Methodsmentioning
confidence: 99%
“…While the exact etiology of OA is unknown, it has been associated with non-bilateral recurring motion injuries on joint surfaces (Bridges, 1992;Bridges, 1995;Cope et al, 2005;Felson, 2004;Felson et al, 1991;Felson and Zhang, 1998;Gramstad and Galatz, 2006;Huiskes, 1982;Jurmain, 1999;Larsen, 2000;Schrader, 2012;Weiss and Jurmain, 2007). OA has been used in prior bioarchaeological research to discuss task-based repetitive motion injuries within joints, estimating motions used over and over again, such as grinding grain or weaving textiles (Bridges, 1989;Bridges, 1991a;Bridges, 1992;Cope et al, 2005;Jurmain, 1999;Kennedy, 1989;Klaus et al, 2009;Larsen, 2000: 107, Pearson andRoberts and Manchester, 1995: 150 and others).…”
Section: Methodsmentioning
confidence: 99%
“…Several factors (e.g. genetic, metabolic) influence the etiology of arthritis including mechanical stress (also influenced by bony abnormalities) (Felson, 2004). Based on epidemiologic studies a general association between occupational tasks and the development of hip osteoarthritis has been previously suggested (Sulsky et al, 2012) and potentially risk associated occupational activities were identified.…”
Section: Introductionmentioning
confidence: 99%
“…OA patients with joint pain are more likely to have effusions, bone marrow lesions, synovial hypertrophy, tendinitis and bursitis around the joint than those patients without the joint pain [18]. Local anesthetic agents are known to reduce pain in periarticular tissues.…”
Section: Sources Of Oa Painmentioning
confidence: 98%